Institutions matter: The role of institutions in the relationship between decision-making power and contraceptive autonomy. - Laura Rossouw; Adeola Oyenubi (PLOS Global Public Health)
Several academic papers have shown that the distribution of household decision-making power has a positive influence on women's contraceptive autonomy. This paper considers the role of the social or institutional environment (as captured by place of residence) in ameliorating or contributing to this relationship. Our study focuses on the context of Nigeria, a country with diverse gender norms and religious practices, often determined by geographic location. For example, Western common law is more prevalent in the southern Nigeria, while Sharia law is largely practiced in the North of the country. The analysis uses the Performance and Monitoring for Action (PMA) dataset (2019-2020), and analysis is done using logistic regressions. We find evidence that the relationship between household decision-making power and contraceptive autonomy is mediated by institutions (city). More specifically, we show that in Lagos-a state characterised by the increasing empowerment of women-women have more contraceptive autonomy as they gain decision-making power in the household. The opposite is true in Kano-household decision-making power has no bearing on contraceptive autonomy.